2021
DOI: 10.1111/jocn.16103
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of seasonal influenza vaccination hesitancy among healthcare personnel: An integrative review

Abstract: Aims and objectives:To explore the determinants of and behaviour change models for seasonal influenza vaccination compliance among healthcare personnel.Background: COVID-19 vaccine hesitancy among healthcare personnel may be better understood by exploring determinants of seasonal influenza vaccine hesitancy. Design: Integrative literature review.Methods: A systematic search was conducted in accordance with PRISMA guidelines.Six thousand and forty-eight articles were screened. Seventy-eight met inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 99 publications
1
10
1
Order By: Relevance
“…In the benefit and barrier dimensions, teachers who disagreed with the negative effects of the influenza vaccine and thought it was effective were more likely to accept the vaccination. These findings were also found among teachers in Poland, 12 Greece 14 and America, 15 and were similar to results from the study of HCWs, 46 elders, 47 and other group of people. 48 , 49 A belief in the efficacy and safety of vaccines was a sign of vaccine confidence.…”
Section: Discussionsupporting
confidence: 89%
“…In the benefit and barrier dimensions, teachers who disagreed with the negative effects of the influenza vaccine and thought it was effective were more likely to accept the vaccination. These findings were also found among teachers in Poland, 12 Greece 14 and America, 15 and were similar to results from the study of HCWs, 46 elders, 47 and other group of people. 48 , 49 A belief in the efficacy and safety of vaccines was a sign of vaccine confidence.…”
Section: Discussionsupporting
confidence: 89%
“… 22–26 Studies have used the HBM to assess parent attitudes toward childhood vaccinations. 27–32 Globally, the HBM has been used to assess general vaccine hesitancy in Nigeria, 33 the United States, 29 and Korea; 30 measles and rubella vaccines in Romania and Japan; 27 , 34 shingles vaccines in the United Kingdom; 35 influenza vaccines in the United States, 36–39 Japan, 27 and Australia; 40 human papilloma virus vaccines in the United States; 28 , 31 , 41–48 and COVID-19 vaccines in the United States, 21 , 44–46 China, 47–53 Bangladesh, 54–56 Turkey, 22 Canada, 23 Vietnam, 57 France, 58 Saudi Arabia, 59 and Pakistan. 60 Several other studies applied HBM to create interventions to increase vaccine knowledge and uptake, 16 and to create new scales of vaccine attitudes and intentions to assess the effectiveness of health campaigns and advertising.…”
Section: Models To Address Vaccine Hesitancymentioning
confidence: 99%
“…The HBM has been used to explore vaccine attitudes about vaccinations with various schedules. The model has been used to assess annual vaccinations; 36 , 40 vaccinations given a few times, such as the human papillomavirus vaccination; 28 , 41 and the childhood vaccination schedule. 29 , 32 While most studies analyze the behaviors of one method of vaccination schedule, a study in Japan explored attitudes toward both influenza and rubella vaccination in tandem.…”
Section: Models To Address Vaccine Hesitancymentioning
confidence: 99%
“…This means that HCWs increased their comprehensive knowledge of IV and showed a favourable attitude; however, they did not change their stubborn opinion about influenza. Many reviews on influenza vaccination consistently indicated that HCWs were hesitant towards IV on the grounds that they were not at risk of contracting influenza and its severe outcomes [ 8 , 22 ]. It is essential to improve HCWs’ perception of the risk of influenza and IV literacy.…”
Section: Discussionmentioning
confidence: 99%